SOLUSI PERSAMAAN DIFERENSIAL PADA SISTEM BEJANA DENGAN MENGGUNAKAN METODE TRANSFORMASI LAPLACE - Ibnas, Risnawati; Hasyim, Putri Resky; Ridwan, Muhammad (Teknosains: Media Informasi Sains dan Teknologi, 2020)
The purpose of this study is to obtain the results of the completion of the Differential Equations in the Vessel System using the Laplace Transform Method. advantage of the Laplace transform is that the initial value problem of a linear differential equation can be solved directly without first determining the general solution and also to obtain the maximum benefit. The model that has been obtained in-vessel systems is homogeneous nonlinear differential equation: if we want to obtain total we must be taken aggregate from a general solution and special solution, the result is